Prenatal maternal sleep and maternal-infant attachment: a systematic review - Crandall, A. J.; Garcia, Mia Ayala; Jones, Neriah; Ayiku, Pearl; Lugo-Candelas, Claudia (Frontiers in Sleep, 2025)
BackgroundMaternal-infant attachment is essential for children's socioemotional and cognitive development. Secure attachment supports emotional regulation, while insecure attachment is linked to adverse mental health outcomes. While prenatal stress and depression are known predictors of attachment, the impact of prenatal maternal sleep is underexplored, despite poor sleep affecting 75% of pregnant individuals by the third trimester. Given the overlap between sleep disturbances, stress, and depression, disrupted sleep may contribute to impaired infant attachment. This systematic review evaluates evidence linking prenatal sleep and maternal-infant attachment.MethodsWe searched PUBMED, Web of Science, EMBASE, PsycINFO, and SCOPUS for studies published from 2000 to 2024. Studies were included if they quantitatively examined associations between prenatal maternal sleep and attachment assessed up to 5 years postpartum. Two reviewers independently screened studies and extracted data. Quality was appraised using the NHLBI tool. Of 2,539 articles, 1,263 unique studies were screened, and only two met the criteria.ResultsBoth studies relied on maternal self-reports. One found prenatal snoring predicted weaker bonding at 6–9 weeks postpartum; another found no direct effects of sleep duration but identified an indirect link to maternal depression. Given limited and mixed findings, further research using objective and subjective sleep measures is needed.